Acupuncture for Chronic Pain-Related Depression: A Systematic Review and Meta-Analysis - Jianyu You; Haiyan Li; Dingyi Xie; Rixin Chen; Mingren Chen (Pain Research and Management)
Objective. The aim of this systematic review was to summarize and evaluate the existing evidence on the effectiveness and safety of acupuncture in relieving chronic pain-related depression (CPRD). Methods. We searched seven online databases to identify eligible randomized controlled trials (RCTs) of acupuncture for CPRD published before September 2020. We included studies that used acupuncture as the intervention group, with or without a control group, and the control group was treated with conventional drugs. Meta-analysis was performed using RevMan 5.3 software. For outcomes, assessments were performed using the Hamilton Depression Scale (HAMD), Visual Analogue Scale (VAS), and adverse events. Results. Eight studies involving 636 participants were identified and included in the meta-analysis. The results showed that single acupuncture treatment and drug treatment have the same effect in improving the HAMD score (MD = −0.14, 95% CI = [−0.88, 0.59], P = 0.71) and alleviating the VAS score (MD = −0.42, 95% CI = [−1.10, −0.27], P = 0.23), but acupuncture treatment is safer (OR = 0.03, 95% CI = [0.01, 0.21], P = 0.0003). In addition, acupuncture combined with drugs (control group) is more beneficial than single-drug treatment in improving the HAMD score (MD = −2.95, 95% CI = [−3.55, −2.36], P < 0.00001) and alleviating the VAS score (MD = −1.06, 95% CI = [−1.65, −0.47], P = 0.0004). Conclusion. Acupuncture is an effective and safe treatment for CPRD, and acupuncture combined with drug therapy is more effective than single-drug therapy. Nevertheless, the conclusions were limited due to the low quality and a small number of included studies.